Kedisiplinan Belajar Peserta Didik dalam Pembelajaran Sejarah Daring di Masa Pandemi dengan Menggunakan Aplikasi Whatsapp Messenger - Tamara Dewi Ramadhani; Erlina Wiyanarti (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2022)
Government policies during the pandemic caused the learning process to turn online. This makes high school teachers, especially in history subjects, have to adjust the lesson plans to the learning media used for teaching. One application that is widely used to carry out online learning is Whatsapp Messenger. In practice, online learning is certainly different from offline learning. Teachers as those who facilitate and monitor students' learning activities will experience difficulties, such as seeing how disciplined students are. Discipline in learning is an important thing to have especially in the 21st century in the process of developing useful skills that can help students when they enter work. Therefore, the teacher designed a lesson plan that contained student learning discipline that they wanted to realize by using whatsapp messenger. This is the background of this research. This study aims to obtain an overview of student learning discipline attitudes, obstacles experienced by teachers and students, as well as what efforts are being made to overcome these problems. The subjects in this study were a history teacher and class X IPA 1 at SMAN 1 Talaga. The research method used is descriptive qualitative, while the data collection technique is done by interview, observation, and documentation study. The results of this study are teacher use the whatsapp messenger application quite optimally, because this can help to carry out history learning during the pandemic. The use of this application is also one of the driving factors that shape student discipline attitudes.